Insight into the Mechanisms of Low Coverage Adsorption of N-Alcohols on Single Walled Carbon Nanohorn - Szymański, Grzegorz Stanisław (Materials (Basel), 2021)
We report for the first time the chromatographic study of n-alcohols (from methanol to butanol) adsorption on single walled carbon nanohorn (SWCNH). Using measured temperature dependence of adsorption isotherms (373–433 K) the isosteric adsorption enthalpy is calculated and compared with the data reported for a graphite surface. It is concluded that a graphite surface is more homogeneous, and the enthalpy of adsorption on SWCNHs at zero coverage correlates well with molecular diameter and polarizability, suggesting leading role of dispersive interactions, i.e., no heteroatoms presence in the walls of SWCNH structures. Next using modern DFT approach we calculate the energy of n-alcohols interactions with a graphene sheet and with a single nanocone finally proposing a more realistic—double nanocone model. Obtained results suggest alcohols entrapping between SWCNH with OH groups located toward nanocones ends, leading to the conclusions about very promising future applications of SWCNHs in catalytic reactions with participation of n-alcohols.